2021
DOI: 10.2196/19915
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Enhanced Patient Instructions for Bowel Preparation Before Colonoscopy: Network Meta-analysis of 23 Randomized Controlled Trials

Abstract: Background Various enhanced patient instructions (EPIs) have been used for bowel preparation (BP) and our previous meta-analysis also demonstrated the efficacy of EPIs in increasing the colonic polyp and adenoma detection rates; however, the optimal method for adequate BP has not yet been developed. Objective We performed a network meta-analysis to determine the optimal instructions. Methods We searched for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…In our meta-analysis, we considered six studies, which confirmed that booklets may enhance the bowel preparation, with an OR of 2.31. A recent meta-analysis found that newly designed booklets were beneficial to improving preparation, but the authors concluded that the evidence was poor due to the number of included studies, which was lower than that in our study [7]. At the end, in our study, we demonstrated that booklets are useful to enhance bowel preparation.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In our meta-analysis, we considered six studies, which confirmed that booklets may enhance the bowel preparation, with an OR of 2.31. A recent meta-analysis found that newly designed booklets were beneficial to improving preparation, but the authors concluded that the evidence was poor due to the number of included studies, which was lower than that in our study [7]. At the end, in our study, we demonstrated that booklets are useful to enhance bowel preparation.…”
Section: Discussioncontrasting
confidence: 90%
“…Adequate comprehension of the preparation and colonoscopy details is a critical contributor to adequate bowel cleansing. Patients usually receive written or verbal instructions from professionals before colonoscopy for details regarding preparation and dietary restrictions, which are defined as standard patient instructions [ 7 ]. However, research by Ness et al found that such guidance often fails to achieve satisfactory bowel preparation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate bowel preparation can lead to prolonged operating time, increased difficulty of colonoscopy, incomplete examination, risk of lesion leakage, and increased risk of complications ( 2 4 ). Therefore, scholars have proposed many solutions to improve bowel preparation quality, including newly designed booklets and telephone re-education ( 5 ). These methods improve bowel preparation quality to a certain extent, but their implementation requires abundant human and material resources.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews were conducted to assess the effects of innovative technology education platforms on the quality of bowel preparation 14 , 15 . However, only the effects of mobile health (mHealth) technologies on colonoscopy preparation outcomes were evaluated in one review.…”
Section: Introductionmentioning
confidence: 99%